EVALUATION OF THE PRESENCE OF CARDIOVASCULAR RISK FACTORS IN UNIVERSITY STUDENTS FROM PORTUGUESE-SPEAKING COUNTRIES - Tibelle Freitas Mauricio; Rafaella Pessoa Moreira; Edmara Chaves Costa; Francisco Mardones dos Santos Bernardo; Paula Alves de Lima; Bonifácio de Jesus Viegas (Universidade Federal do Paraná, 2018)
Objective: to evaluate the presence of cardiovascular risk factors in university students from Portuguese-speaking countries. Methodology: cross-sectional study, carried out from January to July 2017, with 334 students from a federal public university in the state of Ceará, aged 18 years and over, from the following countries: Brazil, Angola, Cape Verde, Guinea-Bissau, Mozambique, Sao Tome and Principe and East Timor. Data was analyzed with the Epi Info version 7.1.2.0 statistical software. Results: of the 334 participants, 75.7% were aged 18-24 years old, 56.9% were Brazilian, 51.8% were female, 47.3% were brown and 47.6% were single individuals with an occasional partner. Risk factors for cardiovascular diseases included a family history of cardiovascular disease (81.1%), sedentary lifestyle (44.3%) and alcohol use (36.2%). Conclusion: identification of the main modifiable and hereditary risk factors in university students could guide actions aimed at promoting cardiovascular health.